Planowanie stopy procentowej do oceny efektywności zabezpieczenia - Krzeszowski, Wojciech Dawid (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
In order to evaluate the effectiveness of hedging for an interest rate it is essential that its future values in particular periods can be calculated. Within the framework of the particular periods changes between planned and actual values will be calculated. The paper is focused on planning the discussed value to this objective. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1175, s. 174-180